HDL Composition, Heart Failure, and Its Comorbidities - Diab, Ahmed; Valenzuela Ripoll, Carla; Guo, Zhen; Javaheri, Ali (Frontiers in Cardiovascular Medicine, 2022)
Although research on high-density lipoprotein (HDL) has been historically focused on atherosclerotic coronary disease, there exists untapped potential of HDL biology for the treatment of heart failure. Anti-oxidant, anti-inflammatory, and endothelial protective properties of HDL could impact heart failure pathogenesis. HDL-associated proteins such as apolipoprotein A-I and M may have significant therapeutic effects on the myocardium, in part by modulating signal transduction pathways and sphingosine-1-phosphate biology. Furthermore, because heart failure is a complex syndrome characterized by multiple comorbidities, there are complex interactions between heart failure, its comorbidities, and lipoprotein homeostatic mechanisms. In this review, we will discuss the effects of heart failure and associated comorbidities on HDL, explore potential cardioprotective properties of HDL, and review novel HDL therapeutic targets in heart failure.